2016
DOI: 10.3109/09273972.2016.1170049
|View full text |Cite
|
Sign up to set email alerts
|

Oculocardiac Reflex during Strabismus Surgery: Experience from a Tertiary Hospital

Abstract: The great majority of patients undergoing strabismus surgery, especially younger subjects, those undergoing operation on cyclovertical muscles, and subjects with higher baseline heart rate, experience OCR during strabismus surgery. During surgery on cyclovertical muscles, the amount of pull is usually more due to more difficult exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…So, it is essential to accurately control the heart rate during ophthalmic surgeries [13]. Different modalities of treatments have been investigated to prevent or alleviate OCR with conflicting findings [27]. This was considered in our study, and it was observed that magnesium sulphate addition completely inhibited the occurrence of OCR reflex.…”
Section: Discussionmentioning
confidence: 81%
“…So, it is essential to accurately control the heart rate during ophthalmic surgeries [13]. Different modalities of treatments have been investigated to prevent or alleviate OCR with conflicting findings [27]. This was considered in our study, and it was observed that magnesium sulphate addition completely inhibited the occurrence of OCR reflex.…”
Section: Discussionmentioning
confidence: 81%
“…Retrobulbar block, premedication with anticholinergics, and gentle tension of muscle traction have been suggested to reduce the rate of OCR [11,15,16]. OCR is known to occur more frequently during MR surgery than during LR surgery, due to differences in the afferent pathways involved; it occurs less frequently under deeper anesthesia [5,7,11,12,17]. In our study, LR and MR did not show differences in the incidence of OCR, in either pediatric or adult patients; moreover, changes in HR during muscle traction were not associated with the depth of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The OCR is defined as a 10-20% reduction in heart rate (HR) from the baseline value or dysrhythmia [1,2,4]. The incidence of OCR ranged from 14% to 90% in previously published studies, depending on the definition used [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 , 4 The incidence of the OCR ranges from 14% to 90% in previously published studies depending on the definition used. 1 , 5 7 In most cases, the OCR resolves without treatment, but some patients develop cardiac arrest and, in very rare cases, sudden death. 8 , 9 The OCR occurs more often in pediatric patients and in those undergoing surgery on the medial rectus (MR) muscle; however, it is less prevalent in pediatric patients when deeper anesthesia is induced.…”
Section: Introductionmentioning
confidence: 99%